Properties Of Recycled Crosslink Polyethylene Filled High Density Polyethylene Composites - Ahmad, Mohammad Shahrulhafiz Basir (2013)
Waste crosslinked polyethylene (XLPE) obtained from a high voltage electric cable was directly utilized, recycled and incorporated into a high density polyethylene matrix. Due to the high gel content (93%), the possibility of producing a completely miscible blend is quite unlikely. However due to that factor, the waste is break down into small filler. They are then compounded with HDPE in concentrations of 5, 10, 15, 20 and 30wt% to produce a composite material. The tensile properties, DSC and morphology of the composite were obtained. However, addition of the waste did not give any reinforcing properties to HDPE matrix. This is visible from the tensile properties of the composite where the tensile strength decreases as the waste concentration increase from 5, 10, 15, 20 and 30%. The elongation at break of the composite decreases as the waste concentration increases from 5, 10, 15, 20 and 30%. The chemical resistance test was done to obtain the tensile properties of before and after immersion. The two chemicals selected are nitric acid and ammonium hydroxide. The tensile strength of the composite decreased compared to virgin HDPE samples. Chemical resistance properties show that overall the tensile strength of the composite decreases with increasing waste concentration from 5, 10, 15, 20 and 30% with chemical concentration of 50 and 100%. For elongation at break of the composite, the value shows irregularity for different waste concentration. Different heating rates of 5, 10 and15°C/min of the DSC scans shows co-crystalization with increasing waste content form 5, 10, 15, 20 and 30%.